Comparing a novel hand held device (Peritron+) to standard urodynamics in measuring intravesical pressure. Issue 3 (11th October 2017) - Ruzhynsky, Vladimir A.; Bitzos, Stephanie; Goping, Ing; Radomski, Sidney B.
Abstract : Aims: Peritron+ is a new handheld device, which can be attached to a urethral catheter to measure intravesical pressures (Pves). The goal of this study was to assess if Pves recorded by standard urodynamics (UDs) are comparable to those recorded by the Peritron+. Methods: Patients with voiding dysfunction and an indication for UD underwent measurement of Pves with nonvideo UD and Peritron+. Pves were recorded at volumes of 50, 100, and 200 mL for the supine and sitting positions. A failure of the Peritron+ was considered to be a discrepancy of Pves values >3 cmH2 O between Peritron+ and UD recordings. Two‐way ANOVA was used to assess for statistical significance. P ‐values < 0.05 were considered significant. Results: Ten female patients, mean age 51 years old, were enrolled in the study. The difference in Pves measurements between Peritron+ and UD were ≤3 cmH2 O at all bladder volumes measured in a supine and sitting positions. There were no adverse events and there were no malfunctions of the Peritron+ device during the study. Conclusions: Peritron+ handheld device accurately assessed Pves at different intravesical volumes when compared to UD measurements. The Peritron+ is a simple and safe device, which can be used in the office by a clinician and at home by a patient to monitor Pves and help to select patients who may require standard UD re‐evaluation. This will be a valuable tool in managing patients with neurogenic and nonneurogenic bladders who are at a risk of upper urinary tract deterioration.